A randomized, double-blind, non-inferiority trial evaluating the efficacy and safety of omarigliptin, a once-weekly DPP-4 inhibitor, or glimepiride in patients with type 2 diabetes inadequately controlled on metformin monotherapy. (3rd October 2017) - Handelsman, Yehuda; Lauring, Brett; Gantz, Ira; Iredale, Carol; O'Neill, Edward A.; Wei, Ziwen; Suryawanshi, Shailaja; Kaufman, Keith D.; Engel, Samuel S.; Lai, Eseng
Abstract: Objective: To evaluate the efficacy and safety of adding the once-weekly DPP-4 inhibitor omarigliptin or the sulfonylurea glimepiride to the treatment regimen of patients with type 2 diabetes (T2DM) and inadequate glycemic control on metformin monotherapy. Methods: Patients with T2DM and HbA1c ≥6.5% to ≤9.0% while on a stable dose of metformin (≥1500 mg/day) were randomized to omarigliptin 25 mg once-weekly ( n = 376) or glimepiride up to 6 mg once daily ( n = 375) for 54 weeks. The primary hypothesis was that omarigliptin is non-inferior to glimepiride in reducing HbA1c at week 54. Results: The mean baseline HbA1c was 7.5% in the omarigliptin group and 7.4% in the glimepiride group. After 54 weeks, the least squares (LS) mean change from baseline in HbA1c was –0.30% in the omarigliptin group and –0.48% in the glimepiride group, with a between-group difference (95% CI) of 0.18% (0.06, 0.30), which met the pre-specified criterion for declaring non-inferiority. The incidence of symptomatic hypoglycemia was 5.3% in the omarigliptin group and 26.7% in the glimepiride group. With the exception of hypoglycemia, the incidences of adverse events and discontinuations were similar between treatment groups. Relative to baseline, omarigliptin was associated with a mean weight loss (−0.4 kg) and glimepiride a mean weight gain (+1.5 kg). Conclusions: After 54 weeks, as add-on therapy to metformin, once-weekly omarigliptin was generally well tolerated and non-inferior to glimepiride in improving glycemic control, with a lower incidence of hypoglycemia and with weight loss vs weight gain.